Sustainability of a Motor Control Exercise Intervention: Analysis of Long-Term Effects in a Low Back Pain Study - Puschmann, Anne-Katrin; Lin, Chiao-I; Wippert, Pia-Maria (Frontiers in Sports and Active Living, 2021)
Development of chronic pain after a low back pain episode is associated with increased pain sensitivity, altered pain processing mechanisms and the influence of psychosocial factors. Although there is some evidence that multimodal therapy (such as behavioral or motor control therapy) may be an important therapeutic strategy, its long-term effect on pain reduction and psychosocial load is still unclear. Prospective longitudinal designs providing information about the extent of such possible long-term effects are missing. This study aims to investigate the long-term effects of a homebased uni- and multidisciplinary motor control exercise program on low back pain intensity, disability and psychosocial variables. 14 months after completion of a multicenter study comparing uni- and multidisciplinary exercise interventions, a sample of one study center (n = 154) was assessed once more. Participants filled in questionnaires regarding their low back pain symptoms (characteristic pain intensity and related disability), stress and vital exhaustion (short version of the Maastricht Vital Exhaustion Questionnaire), anxiety and depression experiences (the Hospital and Anxiety Depression Scale), and pain-related cognitions (the Fear Avoidance Beliefs Questionnaire). Repeated measures mixed ANCOVAs were calculated to determine the long-term effects of the interventions on characteristic pain intensity and disability as well as on the psychosocial variables. Fifty four percent of the sub-sample responded to the questionnaires (n = 84). Longitudinal analyses revealed a significant long-term effect of the exercise intervention on pain disability. The multidisciplinary group missed statistical significance yet showed a medium sized long-term effect. The groups did not differ in their changes of the psychosocial variables of interest. There was evidence of long-term effects of the interventions on pain-related disability, but there was no effect on the other variables of interest. This may be partially explained by participant's low comorbidities at baseline. Results are important regarding costless homebased alternatives for back pain patients and prevention tasks. Furthermore, this study closes the gap of missing long-term effect analysis in this field.